Non-Variceal Upper Gastrointestinal Bleeding - Dong Jin Yoon; Joon Sung Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2024)
Non-variceal upper gastrointestinal bleeding (NVUGIB), which predominantly occurs secondary to peptic ulcers, presents a major challenge in emergency departments and is associated with high mortality rates. The staged approach used for management of NVUGIB comprises preendoscopy, endoscopy, and post-endoscopy. Proton pump inhibitors and prokinetics are used for pre-endoscopy preparation to improve visualization and outcomes. Various endoscopic hemostatic methods, including injection therapy, clipping, and thermal techniques are described, which reflects the need for personalized strategies based on patient conditions and lesion characteristics. Post-endoscopic care includes continuous acid suppression therapy and selective second-look endoscopy. Overall, the approach to effective NVUGIB management is tailored to individual clinical scenarios to optimize patient outcomes.